The successful treatment of Enterocytozoon bieneusi Microsporidiosis with nitazoxanide in a patient with B-ALL: A Case Report - Zhou, Lanlan; Guan, Zebing; Chen, Chaolun; Zhu, Qiuhua; Qiu, Shiqiu; Liu, Yanan; Li, Mingjie; Zeng, Wenbin; Wang, Hong; Gao, Yanmin; Yuan, Yuemei; Zhang, Hanling; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Enterocytozoon bieneusi (E. bieneusi) Microsporidia can cause opportunistic infections in immunocompromised patients and is also an emerging disease in these individuals. Its clinical manifestations are chronic diarrhea and severe wasting syndrome, these can be extremely debilitating and carry a significant risk of death for immunocompromised patients. Often, microsporidia cannot be confirmed immediately by routine examination and culture. Effective and available treatment options are limited for infections caused by E. bieneusi in humans. Such cases are very rare in Chinese Mainland. Case presentation A 47-year-old male had recurrent, profuse watery diarrhea and abdominal discomfort for more than 7 months, with a fever for 5 days. Two years earlier, he received treatment with a modified BFM-90 protocol for acute B cell lymphoblastic leukemia and is currently in the final stages of maintenance therapy with oral methotrexate and mercaptopurine. The leukemia was assessed as still in remission two months ago. PET/CT showed massive peritoneal fluid accumulation and a high uptake area in the diffused peritoneum (SUVmax 12.57), suggesting tumor invasion or microbial infections. However, broad-spectrum antibacterial therapies were ineffective. Metagenomic sequencing of plasma and peritoneal fluid showed no suggestion of the existence of a tumor but instead showed a high sequence number of DNA and RNA of the Microsporidia. His albendazole treatment failed and subsequent treatment with nitazoxanide successfully resolved the infection. Conclusion This case shows that we should consider the possibility of atypical pathogen infection in patients with hematologic malignancy who repeatedly develop unexplained diarrhea with wasting. mNGS can help rule out malignant neoplasms and diagnose infections. Our results suggest that nitazoxanide effectively treats E. bieneusi microsporidia infections.